Conductometric study of nickel chloride in ethanol-water mixed solvent media at various temperatures - Basnet, Nabin; Bhattarai, Ajaya (BIBECHANA, 2014)
The conductivity measurement of nickel chloride has been done in binary solvent of the ethanol-water system. The different percentage of ethanol including 10, 20, 30, 40, 50, 60, 70, 80, 90 and 100 (v/v) has been chosen as binary solvents. The concentration of the electrolyte in the prepared solutions varies from 0.008 to 0.1 mol.l-1 for temperatures 298.15 K, 303.15 K and 308.15 K. The conductivity of the electrolyte decreases with increase in ethanol content in the solvent at a particular temperature, which is due to the decrease in dielectric constant of the medium. The conductivity increases with increase in temperature and concentration, due to increase in mobility of ions and number of ions from observed electrolyte respectively. DOI: http://dx.doi.org/10.3126/bibechana.v12i0.11789 BIBECHANA 12 (2015) 128-134